Analisis Hukum Terhadap Putusan Mahkamah Agung Nomor 987 PK/PDT/2023: Tinjauan Hukum Terhadap Kasus Peninjuan Kembali Dalam Sengketa Hutang Piutang antara Jefri Pratama dan PT. Bank Mandiri (Persero) Tbk Cabang Kota Ternate - Siti Anjani; Fikrotul Jadidah (LPPM Iblam School of Law, 2026)
This study analyzes the legal principles applied in the Supreme Court Decision Number 987 PK/PDT/2023 concerning the judicial review in a debt dispute between Jefri Pratama and PT Bank Mandiri (Persero) Tbk, Ternate Branch. The decision reaffirms fundamental civil law doctrines such as freedom of contract, pacta sunt servanda, good faith, and personal responsibility, emphasizing the contractual obligations of debtors to maintain insurance on collateral. The rejection of the judicial review petition highlights the strict criteria for such extraordinary legal remedies, thereby reinforcing legal certainty and protecting the balanced rights of both debtors and creditors. This research also discusses the implications of the ruling on the legal practice of dispute resolution in banking credit transactions, underscoring the importance of clear contractual clauses and adherence to obligations by both parties. The study concludes with recommendations to improve contractual clarity, debtor education, and judicial prudence in applying judicial review